PERAN LINGKUNGAN SEKOLAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN AGAMA ISLAM DI MAPM CUKIR DIWEK JOMBANG - Dliyaul Hilmi Rumi Al Musaddadah; Sholihul Anshori (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The school environment includes everything around the school, both physical and social, that can affect the student learning process and its outcomes. The school environment is very important in supporting student learning and development. The quality of Islamic religious education is a measure of the goodness or badness of the process and outcomes of Islamic religious learning in an educational institution. This study aims to determine the quality of Islamic Religious Education at MAPM Cukir Diwek Jombang and the role of the school environment in improving the quality of Islamic religious education there. This study is a type of qualitative field research that requires researchers to go to the field to observe natural phenomena. The research method used is Case Study, namely observations of conditions, communities, groups, institutions, or individuals. The study uses interviews, field notes, observations, and documentation as tools. The results of the study indicate that the quality of Islamic religious education at MAPM Cukir Diwek Jombang is good, because it carries out activities such as congregational dhuha prayers and Al-Qur'an mudarosah activities. The school environment supports by providing facilities such as LCDs, PAI books in the library, and PAI extracurricular activities in the form of worship practices guided by competent teachers.